Sensitivity enhancement of graphene Hall sensors modified by single-molecule magnets at room temperature. Issue 4 (4th January 2017) - Zheng, Yuanhui; Huang, Le; Zhang, Zhiyong; Jiang, Jianzhuang; Wang, Kaiyou; Peng, Lian-Mao; Yu, Gui
Abstract : Sensitivity of graphene Hall sensors was enhanced by modifying single-molecule magnets with excellent linearity, off voltage, repeatability and stability. Abstract : Single-molecule magnets (SMMs) possess many unique magnetic properties and thus attract a wide range of attention. However, the applications of SMMs always need a strict atmosphere, i.e. low temperature, high vacuum and strong magnetic field. In this work, we report the preparation and characterization of sensitivity enhanced graphene Hall elements (GHEs) decorated with Tb-core SMMs. By comparing the magnetic sensing and electronic tests of the GHEs before and after the SMMs modifications, the sensitivity of the GHEs increases by 44.9% in voltage mode and 59.0% in current mode compared with pristine GHEs. The increase of sensitivity may result from the magnetic center introduction of SMMs at room temperature. Moreover, the magnetic molecules may affect the graphene field environment leading to a Hall signal change. In addition, the SMMs modified GHEs present excellent linearity, offset voltage, repeatability and stability in magnetic sensing. This study paves the way to apply SMMs into practical use at room temperature and atmospheric pressure without strong magnetic field excitations.